2010
DOI: 10.1364/oe.18.022572
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteric liquid crystal devices with nanoparticle aggregation

Abstract: A broadband cholesteric liquid crystal (CLC) device with a multi-domain structure is demonstrated by using an aggregation of polyhedral oligomeric silsesquioxane (POSS) nanoparticles in the CLC layer. The aggregation pattern of the self-assembled POSS nanoparticles depends on the concentration of POSS doped in the mixture of POSS/CLC and the cooling rate of the mixture from a temperature higher than the clear point. POSS-induced changes in the bulk and surface properties of the cholesteric cells, such as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 14 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…The TIPS of the CLC and PVK is applied to break the planer texture into a polydomain structure, which leads to broadband reflection spectrum. Although the techniques for achieving a broadband CLC device with a poly-domain structure have been demonstrated by polymer network [7] and nanoparticle aggregation, [10] the strong light scattering from the interface between CLCs and PVK (surface scattering) and the refractive index mismatches between the boundaries of the CLC polydomains (volume scattering) also contribute the reflection bandwidth in this work. [11] The CLC cell with reflectance higher than 50% is mainly due to the contribution of surface reflection from the top and bottom glass substrates, which was determined as~14%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TIPS of the CLC and PVK is applied to break the planer texture into a polydomain structure, which leads to broadband reflection spectrum. Although the techniques for achieving a broadband CLC device with a poly-domain structure have been demonstrated by polymer network [7] and nanoparticle aggregation, [10] the strong light scattering from the interface between CLCs and PVK (surface scattering) and the refractive index mismatches between the boundaries of the CLC polydomains (volume scattering) also contribute the reflection bandwidth in this work. [11] The CLC cell with reflectance higher than 50% is mainly due to the contribution of surface reflection from the top and bottom glass substrates, which was determined as~14%.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The conventional CLC devices have two bistable states at zero fields, the Bragg reflection planar and the weakly scattering focal-conic states. The planar texture of CLCs reflects coloured light centred at a wavelength given by λ 0 = nP, where n and P are the average reflective index and pitch of the CLC, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topics that are out of the scope of the review include: multiple bandgaps49–65 for which the reflection consists of the sum of well‐defined (separate) narrow peaks; cells with different colors in the x ‐ y plane of the layer;66–73 broadening of the bandgap such as occurs for light scattering, but not reflection, from a polydomain focal‐conic texture;74 nonequilibrium conditions such as field‐induced,75–80 light‐driven,81–84 stress‐induced,85 or thermally controlled60, 86, 87 broadening of the bandgap. The basic property disappears at the same time as the stimulus, or is not displayed if the temperature program is not followed; increased reflection and coexistence of double‐handed CP reflection bands as an expected consequence of oblique incidence 88–99.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that an LC mixture with polyhedral oligomeric silsesquioxanes (POSS) exhibited vertical alignment without using an alignment layer [4], and the electro-optical characteristics were analysed [5]. The POSS-LC system was applied to ferroelectric LC cells [6], polymer-dispersed LCs [7], cholesteric LCs [8], mixtures with active reactive mesogens [9], a guest-host system [10] and planar alignment [11]. The advantages of the method are apparent; from an industrial point of view, it reduces the number of manufacturing steps, thereby decreasing the manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%